LncRNA XIST promoted the stability of TLR9 mRNA in a FUS-dependent manner to facilitate aerobic glycolysis and proliferation in Th17/CD4+T cells - Wu Yan-ping; Ma Xiao; Han Si-ping; Wang Xiao-qin (Linchuang shenzangbing zazhi)
ObjectiveTo explore the expression and function of lncRNA XIST in Th17 cells in IgA nephropathy （IgAN） and examine the regulation of lncRNA XIST on TLR9 mRNA expression.MethodsCD4+T cells were isolated from peripheral blood mononuclear cells （PBMCs） and induced to differentiate into Th17 cells.XIST was over-expressed and silenced by plasmid transfection.Proliferation and apoptosis of Th17 cells with different levels of XIST expression were detected by flow cytometry and CCK-8 assay.Levels of XIST，TLR9 mRNA and protein were detected by quantitative reverse transcription-polymerase chain reaction （qRT-PCR） and Western blot.The effect of XIST on TLR9 expression was predicted by luciferase report analysis and TLR9 mRNA half-life detection.Potential RNA-binding proteins interacting with XIST were searched through Starbase database and detected by RNA immunoprecipitation and Western blot.GraphPad8.0 was utilized for statistical analysis and variables were expressed as average±SD.Student T test or one-way ANOVA was employed.ResultsXIST was distributed predominantly in cytoplasm.It hinted that XIST might be involved in post-transcriptional regulation.A down-regulation of lncRNA XIST expression promoted apoptosis and DNA damage and arrested cell proliferation by regulating TLR9.With an over-expression of lncRNA XIST，TLR9 expression spiked and XIST up-regulated the expression of TLR9 by promoting the stability of TLR9 mRNA.As an RNA-binding protein （RBP），FUS interacted with XIST and FUS antibodies could significantly enrich XIST transcripts.A down-regulation of lncRNA XIST expression had no effect on FUS protein expression.It suggested that XIST might affect FUS function rather than expression.It was further confirmed that a down-regulation of XIST significantly reduced FUS-TLR9 mRNA binding and FUS over-expression rescued a down-regulation and degradation of TLR9 mediated by si-XIST.ConclusionlncRNA XIST and TLR9 play a critical role in Th17 cell proliferation in IgAN through a FUS-mediated signaling pathway.This finding provides new therapeutic ideas for IgAN..